2017
DOI: 10.1007/s10803-017-3161-x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Anxiety and Insistence on Sameness in Autistic Children: The Role of Sensory Hypersensitivity

Abstract: Sensory hypersensitivity and insistence on sameness (I/S) are common, co-occurring features of autism, yet the relationship between them is poorly understood. This study assessed the impact of sensory hypersensitivity on the clinical symptoms of specific phobia, separation anxiety, social anxiety and I/S for autistic and typically developing (TD) children. Parents of 79 children completed questionnaires on their child's difficulties related to sensory processing, I/S, and anxiety. Results demonstrated that sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 65 publications
8
51
2
Order By: Relevance
“…Sensory issues were also identified as triggers, and were again corroborated as a predictor of self-injury in our quantitative analysis. That both alexithymia and sensory disturbances are predictive of self-injury in autistic people is consistent with the prevalence of these features in other self-harming populations, and with the relationship that both alexithymia and sensory differences show with internalizing symptoms and/or mental ill-health in autism [41][42][43][44][45][46]. Alexithymia is higher than average in adolescent selfharmers and is a well-known correlate of self-injury in clinical populations [47][48][49].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Sensory issues were also identified as triggers, and were again corroborated as a predictor of self-injury in our quantitative analysis. That both alexithymia and sensory disturbances are predictive of self-injury in autistic people is consistent with the prevalence of these features in other self-harming populations, and with the relationship that both alexithymia and sensory differences show with internalizing symptoms and/or mental ill-health in autism [41][42][43][44][45][46]. Alexithymia is higher than average in adolescent selfharmers and is a well-known correlate of self-injury in clinical populations [47][48][49].…”
supporting
confidence: 64%
“…Additionally, it may be that individuals who use NSSI for sensory stimulation are driven more by the correlates or comorbidities of sensory differences rather than the sensory differences per se. Such correlates, in autism, include sociocommunicative abilities, insistence on sameness, cognitive problems and inattention, adaptive behavior, and as previously mentioned, anxiety and other forms of affective difficulties [41][42][43][44][45]. Notably, impulsivity is an intrapersonal factor associated with sensation-seeking through NSSI [73] and with acquired capability for suicide [74], and has indeed been linked to self-injurious behavior [75] and to suicidal acts [25] in autistic children.…”
Section: Discussionmentioning
confidence: 92%
“…In mothers of children with ASD, intolerance for uncertainty mediated the association between anxiety and sensory sensitivity (Uljarević et al, 2016). Black et al (2017) found that sensory hyperresponsivity mediated the relationship between specific phobia and insistence on sameness in children with ASD 7 to 17 years of age.…”
Section: Mediation Modelsmentioning
confidence: 89%
“…RRBs were often proposed as a manifestation of anxiety-driven behaviors, as many authors pointed to the role in which overarousal played in these behaviors. Twelve of these studies included children with ASD, and the relationship between sensory features and RRBs remains across development in this group, including toddlers (Wiggins, Robins, Bakeman, & Adamson, 2009;Wolff et al, 2017), school aged children (Black et al, 2017;Boyd et al, 2010;Matsushima et al, 2016;Neil, Olsson, & Pellicano, 2016), and adolescents (Green, Chandler, Charman, Simonoff, & Baird, 2016). Researchers have attempted to unravel the complexities between specific RRBs, anxiety, and sensory sensitivity.…”
Section: Restricted and Repetitive Behaviorsmentioning
confidence: 99%
“…The emotional difficulties of children with ASD are well reported in the literature and research shows increased negative emotional reactivity and decreased emotion regulation ability in children with ASD compared to typically developing (TD) peers [Mazefsky & White, ]. These emotional difficulties in ASD can be due to factors common among people with ASD such as sensory hypersensitivity [Black et al, ], insistence on sameness [Uljarević, Richdale, Evans, Cai, & Leekam, ], and impaired predictive abilities [Sinha et al, ].…”
Section: Emotional Difficulties In Children With Asdmentioning
confidence: 99%